Neogastropod (Mollusca, Gastropoda) phylogeny: A step forward with mitogenomes - Lemarcis, Thomas; Fedosov, Alexander E.; Kantor, Yuri I.; Abdelkrim, Jawad; Zaharias, Paul; Puillandre, Nicolas (Zoologica scripta, 2022)
The Neogastropoda (Mollusca, Gastropoda) encompass more than 15,000 described species of marine predators, including several model organisms in toxinology, embryology and physiology. However, their phylogenetic relationships remain mostly unresolved and their classification unstable. We took advantage of the many mitogenomes published in GenBank to produce a new molecular phylogeny of the neogastropods. We completed the taxon sampling by using an in‐house bioinformatic pipeline to retrieve mitochondrial genes from 13 transcriptomes, corresponding to five families not represented in GenBank, for a final dataset of 113 taxa. Because mitogenomic data are prone to reconstruction artefacts, eight different evolutionary models were applied to reconstruct phylogenetic trees with IQTREE, RAxML and MrBayes. If the over‐parametrization of some models produced trees with aberrant internal long branches, the global topology of the trees remained stable over models and softwares, and several relationships were revealed or found supported here for the first time. However, even if our dataset encompasses 60% of the valid families of neogastropods, some key taxa are missing and should be added in the future before proposing a revision of the classification of the neogastropods. Our study also demonstrates that even complex models struggle to satisfactorily handle the evolutionary history of mitogenomes, still leading to long‐branch attractions in phylogenetic trees. Other approaches, such as reduced‐genome strategies, must be envisaged to fully resolve the neogastropod phylogeny.